Expanded Neonatal Bloodspot Screening Programmes: An Evaluation Framework to Discuss New Conditions With Stakeholders - Jansen, Marleen E.; Klein, Anne W.; Buitenhuis, Erika C.; Rodenburg, Wendy; Cornel, Martina C. (Frontiers in Pediatrics, 2021)
 Neonatal bloodspot screening (NBS) programmes that screen for rare but serious conditions are expanding worldwide.  Fast developments for testing and treatment put pressure on implementation processes.  In 2015 the Netherlands embarked on an NBS expansion from seventeen to thirty-one conditions.  An evaluation framework was developed based on international NBS frameworks to gain insight in test properties, clinical findings, follow-up and implementation.  A stakeholder process took place with implications for the planning of the expanded NBS panel.  The evaluation framework progressed into a go / no go framework to start national screening, and is currently explored as basis for continuous evaluation of the NBS panel.  The framework and stakeholder process may serve as an example for other programmes.